Poly(vinyl pyrrolidone)-coated graphene/poly(vinylidene fluoride) composite films with high dielectric permittivity and low loss. (16th December 2015) - Li, Hairong; Chen, Zongyi; Liu, Lei; Chen, Jianping; Jiang, Ming; Xiong, Chuanxi
Abstract: A novel nanocomposite with significantly enhanced dielectric properties is reported. This nanocomposite consists of poly(vinyledene fluoride) (PVDF) and poly(vinyl pyrrolidone) anchored reduced graphene oxide (rGO@PVP) nanosheets. The microstructure and dispersion in this nanocomposite were studied by Fourier-transform infrared spectroscopy, thermogravimetric analysis, X-ray photoelectron spectroscopy, atomic force microscopy, X-ray diffraction and scanning electron microscopy. It was found that PVP layer was physically coated on rGO surface and rGO@PVP/PVDF composites exhibited multilaminate nanostructures. The resulted composite films showed high dielectric permittivity and low dielectric loss as well. The dielectric permittivity of the composite reached 622 whereas the dielectric loss was around 0.2 near the percolation threshold at 100 Hz. The PVP surface-functionalized layers were revealed to play important role on enhancing dielectric permittivity and suppressing dielectric loss in this nanocomposite. These results enable the preparation of the percolative dielectric composites with a facile method to exhibit desirable dielectric performances for the highly integrated electronic energy storage applications.